Does It Matter Who Communicates? The Effect of Source Labels in Nuclear Pre‐Crisis Communication in Televised News. (2nd February 2017) - Latré, Edwin; Perko, Tanja; Thijssen, Peter
Abstract : Communication is a crucial aspect of nuclear emergency preparedness. Appropriate public communication about mitigation actions can reduce the radiological health effects during a nuclear emergency. This study tests the impact of communicator credibility on communication effectiveness. It compares the industry, authorities and scientists, by applying an experimental TV news setting in a large‐scale representative face‐to‐face survey ( N =1, 031). Results demonstrate the importance of pre‐crisis communication. Reception and acceptance of the communicated information differed significantly between respondents in the experimental conditions and the control group. However, differences in communicator credibility did not influence the information processing and communication effectiveness. Although communicators were not considered equally credible, they were equally effective in communicating mitigation actions.